Progress of Cancer Nanotechnology as Diagnostics, Therapeutics, and Theranostics Nanomedicine: Preclinical Promise and Translational Challenges - Sultan Alshehri; Syed Sarim Imam; Md. Rizwanullah; Sohail Akhter; Wael Mahdi; Mohsin Kazi; Javed Ahmad (MDPI AG, 2020)
Early detection, right therapeutic intervention, and simultaneous effectiveness mapping are considered the critical factors in successful cancer therapy. Nevertheless, these factors experience the limitations of conventional cancer diagnostics and therapeutics delivery approaches. Along with providing the targeted therapeutics delivery, advances in nanomedicines have allowed the combination of therapy and diagnostics in a single system (called cancer theranostics). This paper discusses the progress in the pre-clinical and clinical development of therapeutics, diagnostics, and theranostics cancer nanomedicines. It has been well evident that compared to the overabundance of works that claimed success in pre-clinical studies, merely 15 and around 75 cancer nanomedicines are approved, and currently under clinical trials, respectively. Thus, we also brief the critical bottlenecks in the successful clinical translation of cancer nanomedicines.